Natural FRCM and Heritage Buildings: Experimental Approach to Innovative Interventions on “Wall Beams” - Riccardo Liberotti; Federico Cluni; Francesco Faralli; Vittorio Gusella (Buildings, 2022)
In this paper, an innovative strengthening system for masonry walls made of externally bonded Fabric-Reinforced Cementitious Matrix (FRCM) is presented. Due to the good mechanical properties and the compatibility with the architectural heritage, the FRCM is an adequate alternative to the use of Fiber-Reinforced Polymer (FRP) composites and other traditional techniques. The proposed system is applied to the strengthening of a classical architectural typology in cultural heritage architecture, which is the “in falso” masonry: a load-bearing wall built over a masonry vault, and hence without a direct load path to the ground. A research program, characterized by an experimental campaign, has been started in order to devise and verify an optimal strengthening system that assures for the masonry wall a structural behavior similar to a “wall beam”, so to prevent progressive collapses when the underlying masonry vault loses its carrier function. In particular, rather than the canonical application, consisting in widespread application to the whole surface of the masonry wall, an innovative intervention made of “Green Tape” of composites has been designed and verified by a specifically designed experimental set-up. The main objective of the research is to propose a reinforcement strategy not detrimental to unmovable artistic assets and tied to the safety and robustness of the architectural heritage.